2006
DOI: 10.1080/08037050600911957
|View full text |Cite
|
Sign up to set email alerts
|

Exercise performance during losartan‐ or atenolol‐based treatment in hypertensive patients with electrocardiographic left ventricular hypertrophy (a LIFE substudy)

Abstract: The objective of the study was to assess the influence of left ventricular (LV) hypertrophy regression on exercise capacity in hypertensive patients. Doppler echocardiography was performed at rest and during exercise in 51 patients with electrocardiographic LV hypertrophy before and after 1 year of randomized blinded losartan- or atenolol-based antihypertensive treatment. After 1 year, blood pressure was comparably reduced by 32/14 and 27/13 mmHg, respectively, in the losartan and atenolol groups, but the aten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…However, similar interactions are not universal. For individuals with left ventricle hypertrophy (Gerdts et al 2006) or right ventricle dysfunction (Dore et al 2005), exercise capacity was not improved with ARB treatment. Moreover, disease states like insulin resistance may be more responsive to ACEi.…”
Section: Arb-exercise Interactionmentioning
confidence: 95%
“…However, similar interactions are not universal. For individuals with left ventricle hypertrophy (Gerdts et al 2006) or right ventricle dysfunction (Dore et al 2005), exercise capacity was not improved with ARB treatment. Moreover, disease states like insulin resistance may be more responsive to ACEi.…”
Section: Arb-exercise Interactionmentioning
confidence: 95%
“…Table 1 shows details of the included studies. 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 Three trials included participants with functional impairment, 4 trials included older people with hypertension or elevated cardiovascular risk, and 1 trial included healthy older men. No trials specifically aimed to recruit participants with sarcopenia or frailty.…”
Section: Resultsmentioning
confidence: 99%
“…Recent literature reviews showed that several drugs that target the renin-angiotensin system have shown beneficial effects on inflammation, skeletal muscle metabolism and oxygen delivery improvement [6,[23][24][25][26]. However, other studies presented contradicting findings [27][28][29][30][31][32][33][34][35][36]. This discrepancy could relate to the studies design (with or without exercise), the type of drug, the participants' characteristics and health status, the study duration, and the outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…The AHTD-users did not perform differently from non-users except that ARB-users showed significantly slightly more time to do the TUG test than did non-users. Other studies of ARB-users who had left ventricle hypertrophy or right ventricle dysfunction suggested no beneficial effects on exercise capacity [35,36]. Some indicated a protective association between ARB use and functional decline [39] while others showed its favourable interaction with exercise, reporting better functional exercise capacity [5].…”
Section: Discussionmentioning
confidence: 99%